PELATIHAN PEMBUATAN SABUN CAIR SEBAGAI UPAYA EFISIENSI PENGELUARAN RUMAH TANGGA DI DESA BANGUN SARI BARU TANJUNG MORAWA - Suhardi Napid; Ahmad Bakhori; Siti Rahmah Sibuea; Rachmat Rizaldi; Junaidi Junaidi; Defaldy Pratama Lubis (Universitas Islam Sumatera Utara, 2026)
This Community Service (PKM) activity aims to improve the knowledge and skills of the community, especially housewives in Bangun Sari Baru Village, Tanjung Morawa District, in producing liquid soap independently. Partners face economic problems in the form of high monthly expenses for the allocation of commercial household cleaning products, such as dish soap and detergent. The method used in implementing this program includes three main stages: (1) education about safe chemical raw materials and family financial management, (2) hands-on training in making liquid soap with an economical and quality formulation. The results of the activity showed a positive response and high enthusiasm from the participants, marked by an increase in partners' understanding of the safe soap-making process by [e.g.: 75%.] Through this new skill, residents of Bangun Sari Baru Village are now able to produce liquid soap independently, which has the potential to save household expenses for cleaning products by [e.g.: 30%-50%] per month. In addition to saving expenses, this activity also opens up opportunities for residents to develop it into a home business to help increase family income.